2013
DOI: 10.1016/j.bmcl.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological activity of diaryl ether inhibitors of Toxoplasma gondii enoyl reductase

Abstract: Triclosan is a potent inhibitor of Toxoplasma gondii enoyl reductase (TgENR), which is an essential enzyme for parasite survival. In view of triclosan’s poor druggability, which limits its therapeutic use, a new set of B-ring modified analogs were designed to optimize its physico-chemical properties. These derivatives were synthesized and evaluated by in vitro assay and TgENR enzyme assay. Some analogs display improved solubility, permeability and a comparable MIC50 value to that of triclosan. Modeling of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…For T. gondii, evidence suggests triclosan may indeed act at least partially through inhibition of FabI, with the compound able to abolish FASII-dependent lipoylation of the PDH complex (see Section 3), and over-expression of the enzyme able to decrease the parasite's susceptibility to the drug [85]. Further efforts have therefore been made to optimize these analogs for use against T. gondii, but few have so far proven sufficiently effective against parasites in vivo [149,[155][156][157].…”
Section: Enoyl-acp Reductase (Fabi)mentioning
confidence: 97%
“…For T. gondii, evidence suggests triclosan may indeed act at least partially through inhibition of FabI, with the compound able to abolish FASII-dependent lipoylation of the PDH complex (see Section 3), and over-expression of the enzyme able to decrease the parasite's susceptibility to the drug [85]. Further efforts have therefore been made to optimize these analogs for use against T. gondii, but few have so far proven sufficiently effective against parasites in vivo [149,[155][156][157].…”
Section: Enoyl-acp Reductase (Fabi)mentioning
confidence: 97%
“…It has been previously shown that the FASII pathway is non essential for malaria during the erythrocytic stage [75,76] . In fact, these studies showed that Pf ENR enzyme was successfully knocked out and the parasites were viable in in vitro culture, showing that this enzyme is dispensable.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified six enzymes as reasonable targets for discovering anti-Toxoplasma agents: i.e., 3MB8 (purine nucleoside phosphorylase) (13), 1LII (adenosine kinase (14), DHRF (dihydrofolate reductase) (15), 4M84 (calmodulin-domain protein kinase 1) (16), 3AU9 (1-deoxy-D-xylulose-5-phosphate reductoisomerase) (17), and 2O2S (enoyl-acyl carrier reductase) (18). Based on the structures deposited in the Protein Data Bank, we analyzed the binding affinities of the active compound 1 and inactive compound 2 s-triazoles to the active sites of the aforementioned enzymes.…”
mentioning
confidence: 99%